Human Genetics to Identify Therapeutic Targets for NAFLD: Challenges and Opportunities - Du, Xiaomi; DeForest, Natalie; Majithia, Amit R. (Frontiers in Endocrinology, 2021)
Non-alcoholic fatty liver disease (NAFLD) encompasses a continuous progression of pathophysiologic stages with varying degrees of reversibility. In addition to the inherent heterogeneity arising from defining discrete stages in a continuous disease process, diagnostic standardization is challenged by a wide variety of diagnostic technologies and proposed criteria including scores derived from liver biopsies, non-invasive imaging, serum biomarkers and varying combinations of these. Nevertheless, NAFLD is heritable, and genetic association studies have successfully identified loci, some of which have shown therapeutic promise. This mini-review provides an overview of the heterogeneity in NAFLD phenotypes and diagnostic methods, discusses genetic variants in relation to the specific stages for which they were identified, and offers a perspective on how the field can advance to better identify targets for drug discovery.